1962
DOI: 10.1192/bjp.108.456.704
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine with electrical treatment in depression—A controlled trial

Abstract: Since the introduction of anti-depressant drugs into general use in the psychiatric field, there have been several statements to the effect that such a drug administered concurrently with electrical treatment reduces the number of shocks required to achieve a satisfactory response. This has been claimed by Sargant (1961) but without experimental support. Dunlop (1960) has published a comparison between the number of electrical treatments given with the anti-depressant drug during a particular attack, and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
2

Year Published

1965
1965
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(62 citation statements)
references
References 3 publications
4
56
2
Order By: Relevance
“…Although these authors did not specifically examine relapse rates, they found no difference between the groups in mean Hamilton Depression Rating Scale (HDRS) scores 6 weeks post-ECT. Further, consistent with previous studies (54)(55)(56), starting antidepressant medication during ECT conveyed no benefit in terms of speed or eventual rate of response (58). Thus, the benefit of simultaneously treating patients with antidepressant medication and ECT to prevent relapse has yet to be proven.…”
Section: Relapse Preventionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although these authors did not specifically examine relapse rates, they found no difference between the groups in mean Hamilton Depression Rating Scale (HDRS) scores 6 weeks post-ECT. Further, consistent with previous studies (54)(55)(56), starting antidepressant medication during ECT conveyed no benefit in terms of speed or eventual rate of response (58). Thus, the benefit of simultaneously treating patients with antidepressant medication and ECT to prevent relapse has yet to be proven.…”
Section: Relapse Preventionsupporting
confidence: 69%
“…Studies undertaken in the 1960s, in which patients took antidepressant medication in conjunction with ECT, found that continuation of the antidepressant after ECT was associated with a 6-month relapse rate of approximately 20%, compared with 50% to 70% in the control groups (54)(55)(56). However, at that time ECT was frequently used as a first-line treatment, and it is possible that some patients in these studies would have responded to the antidepressant medication and remained well on it, even if they had not received ECT.…”
Section: Relapse Preventionmentioning
confidence: 99%
“…As modern studies of more treatmentresistant patients and clearer reporting of methodology began to be conducted, relapse rates rose towards presentday levels. It should be noted that following the publication of three important early trials (Imlah et al, 1965;Kay et al, 1970;Seager and Bird, 1962), with the exception of one small trial in 1984 (Krog-Meyer et al, 1984), no other prospective long-term follow-up studies of continuation pharmacotherapy meeting inclusion criteria were found between 1970 and the early 1990s, perhaps coinciding with diminishing use of ECT. Given this gap in evidence, it is unclear when precisely the shift in relapse rates might have occurred.…”
Section: Relapse Rate At 6 Monthsmentioning
confidence: 99%
“…Three RCTs (Lauritzen et al, 1996;Sackeim et al, 2001;Yildiz et al, 2010) provided extractable data at 3 months and seven (Imlah et al, 1965;Kay et al, 1970;Krog-Meyer et al, 1984;Lauritzen et al, 1996;Sackeim et al, 2001;Seager and Bird, 1962;van den Broek et al, 2006) at 6 months. Relapse rates were 62.7% (95% CI ¼ 47.6-75.8%, I 2 ¼ 0) at 3 months and 65.5% (95% CI ¼ 49.7-78.5%, I 2 ¼ 72%) at 6 months.…”
Section: Relapse Rates In Untreated Samplesmentioning
confidence: 99%
See 1 more Smart Citation